Spider-Man : a new beginning. Book one - Dawson, Delilah S (Marvel action, 2019)
Peter Parker has thrown down with deadly villains and legendary heroes, but high school life might be his greatest challenge yet. Luckily, he has a shot at making the grade with a little help from his new friends... Miles Morales and Gwen Stacy! Collects issues #1-3 of the comic series.